2011
DOI: 10.1371/journal.pone.0025616
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of the Development of Separate Representations of Facial Identity and Expression in the Primate Visual System

Abstract: Experimental studies have provided evidence that the visual processing areas of the primate brain represent facial identity and facial expression within different subpopulations of neurons. For example, in non-human primates there is evidence that cells within the inferior temporal gyrus (TE) respond primarily to facial identity, while cells within the superior temporal sulcus (STS) respond to facial expression. More recently, it has been found that the orbitofrontal cortex (OFC) of non-human primates contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…The best performing models are deep neural nets and they are also best at explaining the IT representational geometry (Khaligh-Razavi et al 2014;Cadieu et al 2014). Khaligh-Razavi et al (2014) tested a wide range of classical computer vision features, several neuroscientifically motivated vision models, including VisNet (Wallis & Rolls 1997;Tromans et al 2011) and HMAX (Riesenhuber & Poggio 1999), and the deep neural network of Krizhesvsky et al (2012; Fig. 3).…”
Section: Early Studies Testing Deep Neural Nets As Models Of Biologicmentioning
confidence: 99%
“…The best performing models are deep neural nets and they are also best at explaining the IT representational geometry (Khaligh-Razavi et al 2014;Cadieu et al 2014). Khaligh-Razavi et al (2014) tested a wide range of classical computer vision features, several neuroscientifically motivated vision models, including VisNet (Wallis & Rolls 1997;Tromans et al 2011) and HMAX (Riesenhuber & Poggio 1999), and the deep neural network of Krizhesvsky et al (2012; Fig. 3).…”
Section: Early Studies Testing Deep Neural Nets As Models Of Biologicmentioning
confidence: 99%
“…However, these previous theoretical and experimental studies do not explain the precise learning mechanisms by which these neuronal representations of global attributes, such as identity and expression, may become mapped onto separate processing areas in the later stages of the visual system. Recently, Tromans et al (2011) developed the first neural network model demonstrating how physically separated representations of facial identity and expression may develop through a biologically plausible process Figure 2. Physiological evidence from the single unit recording study carried out by Freiwald et al (2009) showing neuronal selectivity for the spatial relationships between facial features with monotonic tuning curves.…”
Section: Representations Of Global Attributes Of Facesmentioning
confidence: 99%
“…The important question is how such selective cell response properties could develop given that the visual system is always exposed to both facial identity and expression simultaneously during early visually guided learning and self-organization in the visual system. In earlier work carried out by Tromans et al (2011), it was shown that when VisNet was trained on a large number of faces, the higher layers of the model developed neurons that either responded to the identity of a face regardless of its emotional expression, or responded to the facial expression irrespective of facial identity. The hypothesized learning mechanism was as follows.…”
Section: How Some Neurons In Later Stages Of Visual Processing Learn mentioning
confidence: 99%
See 1 more Smart Citation
“…These authors argued that the functional dissociation between facial expression and identity related directly to the fact that these two facial characteristics load on different dimensions of the stimulus. These arguments for the fractionated processing of structural information about face identity and emotion have recently been bolstered by computational work that has suggested that independent processing of these two types of information is a natural consequence of the statistical independence between the image features for structural identity and emotion (Tromans, Harris, & Stringer, 2011).…”
mentioning
confidence: 99%